Isolated benign cerebral vasculitis or migrainous vasospasm?. Issue 1 (January 1984) - Serdaru, M; Chiras, J; Cujas, M; Lhermitte, F
Abstract : A 39-year-old woman experienced severe headache, epilepsy and rapidly progressive aphasia and hemianopia. Carotid angiograms displayed segmentary narrowing of intracranial arteries as previously described in benign cerebral vasculitis. Her superficial temporal artery was also involved, allowing a biopsy of the abnormal part of the vessel. Microscopical study of this artery was normal. A second carotid angiogram, 14 days later, showed normal intracranial arteries. These findings suggest arterial spasm rather than distal arteritis.